2011
DOI: 10.1016/j.bandc.2011.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and dichotic listening: Evidence from the study of menstrual cycle effects

Abstract: a b s t r a c tThis report presents evidence for changes in dichotic listening asymmetries across the menstrual cycle, which replicate studies from our laboratory and others. Increases in the right ear advantage (REA) were present in women at phases of the menstrual cycle associated with higher levels of ovarian hormones. The data also revealed correlations between hormone levels and behavioural measures of asymmetry. For example, the pre-ovulatory surge in luteinising hormone (LH) was related to a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
5
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 28 publications
2
27
5
2
Order By: Relevance
“…In contrast to the majority of studies investigating menstrual cycle effects on language lateralisation as measured by DL (Cowell et al, 2011;Wadnerkar et al, 2008;Sanders and Wenmoth, 1998), the current study found a reduction in lateralisation when estradiol and progesterone levels were high, regardless of the attention condition. As different attention conditions were used, resulting in either LEAs or REAs, it is unlikely that the general reduction in language lateralisation is due to sex hormones selectively affecting one hemisphere.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the majority of studies investigating menstrual cycle effects on language lateralisation as measured by DL (Cowell et al, 2011;Wadnerkar et al, 2008;Sanders and Wenmoth, 1998), the current study found a reduction in lateralisation when estradiol and progesterone levels were high, regardless of the attention condition. As different attention conditions were used, resulting in either LEAs or REAs, it is unlikely that the general reduction in language lateralisation is due to sex hormones selectively affecting one hemisphere.…”
Section: Discussioncontrasting
confidence: 99%
“…In conclusion, in contrast to previous studies (Hjelmervik et al, 2012;Cowell et al, 2011;Sanders and Wenmoth, 1998;Wadnerkar et al, 2008), the present study revealed a reduced lateralisation in women with high levels of estradiol and progesterone across all DL conditions. This suggests that the proposed estradiol-related improvements in cognitive control may be smaller than previously reported (Hjelmervik et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…18,19,20 Na coleta da saliva, é verificada a concentração dos esteroides livres que estão presentes na circu- Quanto aos resultados dos testes de escuta dicótica, pode-se observar nas pesquisas uma prová-vel influência dos hormônios esteroides ovarianos na percepção auditiva. 12,13,14,15,16,17,18 Um estudo utilizou o teste de escuta dicótica consoante-vogal (CV) em mulheres durante o ciclo menstrual, demonstrando melhor desempenho na orelha direita na fase lútea média, em comparação com a fase menstrual. O autor justifica que o nível elevado de estrogênio na fase lútea média reforça a função do hemisfério esquerdo, resultando em vantagem da orelha direita.…”
Section: Discussionunclassified